PROGRAM COMMUNITY DEVELOPMENT CIREBON POWER SEBAGAI UPAYA MEMUTUS RANTAI KETERGANTUNGAN NELAYAN TERHADAP TENGKULAK - Suwandi, Maygsi Aldian; Harlyandra , Yorri (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
Fisherman identical with poverty. One of the reason of fisherman poverty problem is that they are very dependant to tengkulak in their lives. The relation between tengkulak dan fisherman isn’t just about economic but also socio cultural relation that rooted since long time ago. One of PT Cirebon Electric Power CSR empowerment program that try to solve that fisherman problem is Jelombang Selar Fisherman Group program. The program initiated to increase the welfare of fisherman by helping them out of their relation with middleman (tengkulak). This research used qualitative methods with phenomenology approach. Data collected through interview and observation. Analysis of the research using CSR empowerment approach. The result showed in order to increase people empowerment done by giving alternative income generating activity, giving charitative assistance that help in short time as energy to empower, increasing individual and institutional capacities to optimalize local resources, increasing people self reliability by building kiosk and fish market and collaborate with government for sustainability. Corporate program meant for individual and institution. It was done to create empowerment program that sustainable and grew self reliance for people. Corporate also able to grew awareness of people to contribute voluntarily and minimize punishment as push factor.